Virus reactivation: a panoramic view in human infections. (April 2011) - Traylen, Christopher M; Patel, Hersh R; Fondaw, Wylder; Mahatme, Sheran; Williams, John F; Walker, Lia R; Dyson, Ossie F; Arce, Sergio; Akula, Shaw M
Viruses are obligate intracellular parasites, relying to a major extent on the host cell for replication. An active replication of the viral genome results in a lytic infection characterized by the release of new progeny virus particles, often upon the lysis of the host cell. Another mode of virus infection is the latent phase, where the virus is ''quiescent'' (a state in which the virus is not replicating). A combination of these stages, where virus replication involves stages of both silent and productive infection without rapidly killing or even producing excessive damage to the host cells, falls under the umbrella of a persistent infection. Reactivation is the process by which a latent virus switches to a lytic phase of replication. Reactivation may be provoked by a combination of external and/or internal cellular stimuli. Understanding this mechanism is essential in developing future therapeutic agents against viral infection and subsequent disease. This article examines the published literature and current knowledge regarding the viral and cellular proteins that may play a role in viral reactivation. The focus of the article is on those viruses known to cause latent infections, which include herpes simplex virus, varicella zoster virus, Epstein––Barr virus, human cytomegalovirus, human herpesvirus 6, human herpesvirus 7, Kaposi''s sarcoma-associated herpesvirus, JC virus, BK virus, parvovirus and adenovirus.